Comparison of GPS receivers - See, Jerrick Wei Xiang. (2009)
This final year report is a written report of the student during his one year module of EE3079, final year project module for the year 2008/2009. The student was involved in the project, Comparison of GPS Receivers, in the Information Systems Research Lab undertaken by A/P Saman S Abeysekera. This project report provides a detailed research and technical knowledge of the accuracy of commercial GPS receivers and the application of GPS for traffic monitoring and vehicle guidance system. This report is limited to the present technology available and the current GPS receivers selected. This project report will briefly describe the application methods of the GPS coordinate system, Radar technology and GPS receivers. It will also look into the location calculation process of calculating the GPS coordinates. Research was done to investigate the possibilities of applying GPS system to complex applications like automated driven vehicle.